Mononucleosis infecciosa. Casuística hospitalaria. - Cruz Romero, Felix; Collado Llanes, María de los Ángeles; Bisquet Hernández, Clara; Romero Hernández, Miguel (Revista Cubana de Pediatría, 2023)
Se estudian 72 pacientes con diagnóstico de mononucleosis infecciosa.